Flag of the Hamlet of Aklavik ... - Farnel, Sharon (University of Alberta Library, 2017)
This flag of the Hamlet of Aklavik was displayed in a public building. It is yellow with black bars on either side of a circle which surrounds a triangular shield on which there is a door mouse below an open book. The words "Never Say Die" appear in an arc below the shield. The words Hamlet of Aklavik appear in in arc above the shield. ...